Business Performance of MSMES in Traditional Market: an Analysis of Strategic Management Aspect - Rahmawati, Rahmawati; Arifah, Siti; Pujiasmanto, Bambang; Goestjahjanti, Francisca Sestri; Nurlaela, Siti; Badriyah, Nurul (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2023)
This study aims to analyze the performance of MSME businesses in the Bahulak Market, Karungan Plupuh, Sragen, from a strategic management perspective. This research uses quantitative methods. Primary data sources were obtained by distributing questionnaires to business actors and MSME owners in Karungan Village, Plupuh, Sragen. The population that was the target of this study were SMEs registered in Karungan Village with a total of 74 businesses. The sampling technique used is simple random sampling. Data analysis used the Structural Equation Modeling (SEM) approach. This study succeeded in concluding that the production strategy, HR strategy, and development research strategy have a positive effect on business performance. In addition, business actors in the Bahulak Plupuh Market in Sragen still need assistance from various related parties to further develop the business they are running. This research is important to be carried out to encourage the Pasar Bahulak Tourism Village, including that the products produced are absorbed by the market.